Synthesis and Structural Study of a Novel La0.67Ca0.33Cr0.9Cu0.1O3-? Anode for Syngas-Fuelled Solid Oxide Fuel Cell - Radenahmad, Nikdalila; Afif, Ahmed; Reza, Md Sumon; Afroze, Shammya; Park, Jun Young; Zaini, Juliana; Taweekun, Juntakan; Azad, Abul Kalam (International Journal of Integrated Engineering, 2021)
Solid oxide fuel cell (SOFC) is an alternative energy generation device that converts chemical energy into electrical energy from the use of hydrogen or hydrogen-rich fuel. A light hydrocarbon, e.g. methane (CH4), is a hydrogen-rich fuel that can be used as an alternative fuel to hydrogen in SOFC application. Carbon-containing fuel is accessible from natural gas, biogas, biomass gasification, etc. Biomass gasification produces methane, hydrogen (H2), etc. as syngas products which could be integrated with SOFC. As anode is an outer layer of SOFC which exposes to fuel, the development of anode for carbon-containing fuel application is essential. Conventional Ni-containing anode is found to create carbon deposition which degrades the cell. The replacement of copper (Cu) to Ni has been studied to enhance the direct electrochemical oxidation of dry hydrocarbons which is free from carbon deposition. With the interest of Cu doping, a La-based anode has been doped with 10 % Cu at B-site of perovskite structure as La0.67Ca0.33Cr0.9Cu0.1O3-? and studied the X-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersive X-ray (EDX) for future application in syngas-fuelled SOFC.